Blueberries for Sal - McCloskey, Robert, 1914-; Weston Woods Studios (Weston, Conn. : Weston Woods Studios, 1971)
Little Sal and Little Bear gently portray the common needs of man and beast in this story about blueberrying in Maine.
CRD0041BS.
Book published: New York : Viking Press, c1948.
Issued also (p1964) as: 1 disc (8 min., 40 sec.) : 33 1/3 rpm ; 7 in.
Keywords: Bears -- Fiction; Bears -- Fiction; Maine -- Fiction; Maine -- Fiction